Exploring the Evolution of AR Technologies: A Comprehensive Review of Recent Literature (2019-2023) - Purba, Siska Wati Dewi; John Jackson Yang (Yayasan Pendidikan Mandira Cendikia, 2024)
This research is motivated by the need to provide a comprehensive and up-to-date understanding of the state-of-the-art in AR (AR) technologies. The last five years (2019-2023) have witnessed unprecedented growth in AR applications in education fields. Thirty out of 191 published Social Science Citation Index articles from 2019 to 2023 were reviewed with a coding scheme. The findings reveal that the science subject predominates among the various subjects discussed, with 80% of researchers opting to conduct experiments inside the classroom, demonstrating a fourfold preference over those conducted outside. The mobile platform emerges as the most widely discussed platform, capturing the attention of 47% of researchers. Examining the roles of AR, teaching agents hold the highest percentage at 81.3%, followed by motivational agents at 15.6% and peer agents at 3.1%. Furthermore, the role of a teacher as a facilitator stands out as the most prevalent among the various teacher roles discussed. In terms of research methods, experimental and quantitative approaches are prominent, each accounting for 33.3%. The study delves into the user performance aspect, indicating that users demonstrate higher efficiency and quality in designing materials using AR material design systems compared to traditional synthetic systems. Notably, a significant portion of research is conducted in the middle of secondary school settings (33.3%), with a predominant research duration falling between 2 weeks to 1 month (36.7%). In terms of data collection, the pre-test and post-test method prevails, constituting 74.4% of cases. The positive impact of AR implementation is evident in increased understanding, self-efficacy, and favorable attitudes. This abstract provides a concise summary of key trends and findings, contributing valuable insights to the ongoing discourse on AR in education.